APPLICATION OF INQUIRY LABORATORY LEARNING MODELS TO IMPROVE SCIENCE AND SCIENCE PROCESS LEARNING (Research in Chemistry Subjects in class X IPS at SMAN 2 Lebong) - Ana Marleni; Bambang Sahono (DIADIK, 2019)
This study describes the application of laboratory inquiry learning models to improve science process skills, learning achievement, and the effectiveness of the application of laboratory inquiry learning models in improving student learning achievement by using Classroom Action Research and quasi-experimental methods. The subjects of the study were students of IPS1 class X SMA 2 LEBONG with 28 students while the population and the sample were class X IPS2 as the experimental class and class X IPS 3 consisting of 28 students as the control class. The research sample used the observation method using the observation sheet teacher activities and sheets observation of science process skills, written tests to measure student learning achievement. Data analysis using the average formula and paired sample t-test and independent samples. Based on the results of the study and the results of the analysis show that the application of the laboratory inquiry learning model is able to improve science process skills and student learning achievement, and the laboratory inquiry learning model is more effective in improving student achievement in Chemistry subjects compared to conventional learning.